Development of Near-Isogenic Lines in a Parthenogenetically Reproduced Thrips Species, Frankliniella occidentalis - Yuan, Guangdi; Wan, Yanran; Li, Xiaoyu; He, Bingqing; Zhang, Youjun; Xu, Baoyun; Wang, Shaoli; Xie, Wen; Zhou, Xuguo; Wu, Qingjun (Frontiers in Physiology, 2017)
Although near-isogenic lines (NILs) can standardize genetic backgrounds among individuals, it has never been applied in parthenogenetically reproduced animals. Here, through multiple rounds of backcrossing and spinosad screening, we generated spinosad resistant NILs in the western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), with a haplo-diploid reproduction system. The resultant F. occidentalis NIL-R strain maintained a resistance ratio over 30,000-fold, which was comparable to its parental resistant strain, Spin-R. More importantly, F. occidentalis NIL-R shared 98.90% genetic similarity with its susceptible parental strain Ivf03. By developing this toolset, we are able to segregate individual resistance and facilitate the mechanistic study of insecticide resistances in phloem-feeding arthropods, a group of devastating pest species reproducing sexually as well as asexually.